Barriers to the Recognition of Geriatric Depression in Residential Care Facilities in Alberta. (2nd October 2020) - Azulai, Anna; Hall, Barry L.
Abstract: This study explored the barriers that regulated nurse professionals encountered in recognizing and assessing geriatric depression in residential care facilities in the Canadian province of Alberta. The study used a convergent parallel mixed methods design, including a cross-sectional survey ( N = 635) and qualitative interviews ( N = 14) with regulated nurse professionals. Findings revealed six major barriers to the recognition of geriatric depression in Alberta, including 1) insufficient clinical knowledge and training in geriatric depression; 2) misconceived beliefs about geriatric depression; 3) limited access to resources; 4) unclear depression assessment protocol and procedures in facilities; 5) characteristics of models of care and organizational culture in facilities; and 6) communication difficulties among all stakeholders in the process. Socio-cultural values and beliefs about geriatric depression played a key role in the complex interaction of the various structural and agential barriers to the effective recognition and assessment of depression in residential care facilities in Alberta.